2022
DOI: 10.3390/ijms23105459
|View full text |Cite
|
Sign up to set email alerts
|

Truncated O-Glycan-Bearing MUC16 Enhances Pancreatic Cancer Cells Aggressiveness via α4β1 Integrin Complexes and FAK Signaling

Abstract: Elevated levels of Mucin-16 (MUC16) in conjunction with a high expression of truncated O-glycans is implicated in playing crucial roles in the malignancy of pancreatic ductal adenocarcinoma (PDAC). However, the mechanisms by which such aberrant glycoforms present on MUC16 itself promote an increased disease burden in PDAC are yet to be elucidated. This study demonstrates that the CRISPR/Cas9-mediated genetic deletion of MUC16 in PDAC cells decreases tumor cell migration. We found that MUC16 enhances tumor mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Deletion of MUC16 decreases tumor cell migration in pancreatic ductal adenocarcinoma cells [46], which is in line with the decrease in proliferation and migratory ability in MUC16silenced YTS-1 cells. MUC16 bearing truncated O-glycans exacerbates malignancy by FAK activation through interactions with integrins on cell membranes [46], indicating that O-glycans might regulate the localization and turnover of target proteins and be involved in cancer progression.…”
Section: Discussionsupporting
confidence: 75%
“…Deletion of MUC16 decreases tumor cell migration in pancreatic ductal adenocarcinoma cells [46], which is in line with the decrease in proliferation and migratory ability in MUC16silenced YTS-1 cells. MUC16 bearing truncated O-glycans exacerbates malignancy by FAK activation through interactions with integrins on cell membranes [46], indicating that O-glycans might regulate the localization and turnover of target proteins and be involved in cancer progression.…”
Section: Discussionsupporting
confidence: 75%
“…In breast cancer metastasis, DKK1 is a serum marker that promotes breast cancer bone metastasis by Frontiers in Pharmacology frontiersin.org regulating the WNT signaling pathway (Zhuang et al, 2017). Moreover, MUC16 is associated with PDAC malignant progression, and that truncated O-glycans containing MUC16 activate FAK signaling through specific interactions with α4 and β1 integrin complexes on cancer cell membranes, contributing to PDAC malignancy progress (Rajesh et al, 2022). Frontiers in Pharmacology frontiersin.org…”
Section: Discussionmentioning
confidence: 99%
“…Rajesh et al. revealed that in PDAC, truncated O-glycan forms of MUC16 interact with the α4β1 integrin complex, activating the ILK/FAK signaling pathway and enhancing tumor invasiveness ( 68 ). Muniyan et al.…”
Section: The Relevance Of Muc1 and Muc16 To Tumor Development And Pro...mentioning
confidence: 99%